2007
DOI: 10.1101/lm.527207
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone time-dependently modulates β-adrenergic effects on long-term potentiation in the hippocampal dentate gyrus

Abstract: Previous experiments in the hippocampal CA1 area have shown that corticosterone can facilitate long-term potentiation (LTP) in a rapid non-genomic fashion, while the same hormone suppresses LTP that is induced several hours after hormone application. Here, we elaborated on this finding by examining whether corticosterone exerts opposite effects on LTP depending on the timing of hormone application in the dentate gyrus as well. Moreover, we tested rapid and delayed actions by corticosterone on ␤-adrenergic-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 61 publications
(73 reference statements)
4
46
1
Order By: Relevance
“…Effects of maternal deprivation on synaptic plasticity in the dentate gyrus Low excitability of DG granule neurons in vitro is due to strong GABAergic inhibition and a hyperpolarized resting membrane potential (Wisden et al, 1992;Coulter and Carlson, 2007), making it difficult to induce LTP (Pu et al, 2007). Here, significant potentiation only occurred in the presence of the GABAergic antagonist bicuculline.…”
Section: Effects Of Maternal Deprivation On Adult Neurogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of maternal deprivation on synaptic plasticity in the dentate gyrus Low excitability of DG granule neurons in vitro is due to strong GABAergic inhibition and a hyperpolarized resting membrane potential (Wisden et al, 1992;Coulter and Carlson, 2007), making it difficult to induce LTP (Pu et al, 2007). Here, significant potentiation only occurred in the presence of the GABAergic antagonist bicuculline.…”
Section: Effects Of Maternal Deprivation On Adult Neurogenesismentioning
confidence: 99%
“…Sections containing the rostral part (Ϫ2.5 to Ϫ4.0 mm from bregma) (Paxinos and Watson, 1986) of the hippocampal dentate gyrus were placed in a recording chamber maintained at 30 -32°C with a constant flow of oxygenated aCSF. Field EPSPs (fEPSPs) were recorded as described previously (Pu et al, 2007;Bagot et al, 2009) in the absence or presence of the GABAergic antagonist bicuculline methiodide (10 M; Tebu-bio). fEPSPs were evoked using a stainless steel bipolar stimulation electrode (60 m diameter, insulated except for the tip) positioned in the medial perforant pathway and recorded through a glass electrode (2-5 M⍀ impedance, filled with aCSF) positioned in the middle third of the molecular layer of the upper blade.…”
Section: Methodsmentioning
confidence: 99%
“…However, experiments in which the two hormones were not given concurrently showed that glucocorticoids may otherwise suppress the noradrenergic effect (Borrell et al 1984). This suggests that the interactive hormonal functions affecting the memory systems are not always uniform.Support for this nonuniformity was recently obtained in the hippocampal DG (Pu et al 2007). Corticosterone time-dependently modulated noradrenergic action on long-term potentiation (LTP), the best-described neurobiological substrate of learning and memory to date (Goosens and Maren 2002;Martin and Morris 2002;Morris 2003).…”
mentioning
confidence: 99%
“…Corticosterone time-dependently modulated noradrenergic action on long-term potentiation (LTP), the best-described neurobiological substrate of learning and memory to date (Goosens and Maren 2002;Martin and Morris 2002;Morris 2003). Thus, b-adrenergic facilitation of LTP was accelerated if corticosterone was coapplied with the b-agonist isoproterenol, but suppressed if corticosterone was transiently applied several hours before the b-agonist (Pu et al 2007). In view of the behavioral observations that b-agonists and glucocorticoids both affect memory processes involving the BLA (Roozendaal et al 2002), we here investigated the time-dependent hormonal actions in this region.…”
mentioning
confidence: 99%
See 1 more Smart Citation